Gas phase selective propylene epoxidation over La2O3-supported cubic silver nanoparticles. Issue 13 (7th June 2019) - Yu, Bin; Ayvalı, Tuğçe; Wang, Zhi-Qiang; Gong, Xue-Qing; Bagabas, Abdulaziz A.; Tsang, S. C. Edman
Abstract : It is shown that the Ag nanocube/La2 O3 interface catalyses gas phase oxidation of propylene to propylene oxide cooperatively with enhanced selectivity and conversion. Dioxygen is preferentially activated and dissociated by La2 O3 (001) and the active atomic oxygen over the Ag(100) facet leads to selective propylene epoxidation. Abstract : Herein, we present a systematic study on geometric and electronic effects exhibited by exposed Ag faceted nanoparticles and supports in the direct catalytic propylene epoxidation from O2 and propylene. Ag nanoparticles were first synthesised with well-defined morphologies (nanocubes or nanospheres) before they were placed on various supports, including conventional Al2 O3 and a series of lanthanide oxides (Ln2 O3 ). Results showed that faceted Ag nanoparticles and the oxide supports on their own are unable to deliver decent propylene oxide (PO) selectivity. However, their interfaces such as Ag nanocubes/La2 O3 can dramatically enhance PO conversion (11.6%) and selectivity (51%) under dilute gas stream (3.33% C3 H6 : 1.67% O2 : 95% He) at atmospheric pressure and 270 °C temperature. It is envisaged that the exposed (001) polar face on La2 O3 with a higher density of oxygen vacancies facilitates dioxygen dissociation and the dissociated active oxygen is transferred to the Ag(100) surface at the interface where longer Ag–Ag interatomic distances prevent the removal of γ-H of propylene towards combustion, thus accounting for higher PO selectivity. These findings may lead to the design of new supported silver catalysts for environmentally-benign propylene oxide production.